(untitled) (Itinera, 2021)
My article aims to interrogate the tension between space and time in Diderot’s philosophy starting from the tableau of the imagination and its specific functioning. By examining the category of ragoût – a culinary preparation that, during the 18th century, became an expression of an aesthetic of the relationship and harmony between the parts and the whole – I will show how it plays, between the Lettres sur les souds et muets, the Essais sur la peinture, the Salons and the Regrets sur ma vieille robe de chambre, its central role in defining an idea of dynamic spatiality, within which reality and representation coexist in relationships of mutual tension and correspondence. In fact, the ragoût reveals a conception of convenience which, by interweaving space and time, recalls the processes of human reason and interrogates them in pictorial and real space, making it habitable and comprehensible: if a detail always reveals a totality, activating a process of orientation in reality, when the relationship between the parts and the whole breaks down, the world itself falls apart. It is the law of convenience and ragoût that regulates the world: to change one’s dressing gown is to redefine one’s life entirely. If this does not happen, if the relationship between the fragment and the whole is broken, as in La Grenée painting exhibited at the Salon 1767, Penelope appears more suited to a beer hall than to the majestic but sober palace of Ithaca.